Intra-Skip in Inter-Frame Coding of H.264/AVC - Hui Su (International Journal of Digital Multimedia Broadcasting)
In inter-frame coding of H.264/AVC standard, not only seven inter-partition modes but also intra-modes are taken into account for seeking the best coding mode so as to maintain higher encoding efficiency by sacrificing the speed of H.264/AVC encoder. Aiming at intra-skip, this paper proposes a novel mathematical model for intra-skip in inter-frame coding to alleviate the complexity of the process; the model provides remarkable performance increment by cutting down encoding time while accompanying very minor bitrate increase. The critical advantage of this proposed scheme most emphasized on is that it can optimize H.264 encoder in conjunction with any proposed fast inter- and intra-methods which are focusing on inter-partition mode decision, motion search algorithms, and fast intra-algorithms.